2019
DOI: 10.1002/jmv.25392
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of enteric viruses associated with acute gastroenteritis in pediatric patients in a low‐income area in Vitória, Southeastern Brazil

Abstract: Acute gastroenteritis (AGE) is a significant cause of child mortality worldwide. In Brazil, despite the reduction in infant mortality achieved in recent years, many children still die because of undiagnosed AGE. The prevalence, viral load, and circulating genotypes of rotavirus A (RVA), human adenovirus (HAdV), and norovirus GII (NoV GII) were investigated in children with AGE during 12 months in Vitoria, Espírito Santo, Southeastern Brazil. Enteric viruses were detected in stool samples, quantified by quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In Brazil, some studies performed pre- and post-rotavirus vaccine introduction reported HAdV detection rates ranging from 3.9 to 6.8%, indicating a minor impact of HAdV as an etiologic agent of AGE in Brazil 29 31 . In contrast, but similar to our findings, data from two recent studies conducted in Northern and Southeastern Brazil reported HAdV detection rates of 28.6% and 18.5%, respectively, among children with AGE symptoms 32 , 33 . Another study in Northern Brazil has detected HAdV in 50% of stool samples from hospitalized children with AGE 34 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Brazil, some studies performed pre- and post-rotavirus vaccine introduction reported HAdV detection rates ranging from 3.9 to 6.8%, indicating a minor impact of HAdV as an etiologic agent of AGE in Brazil 29 31 . In contrast, but similar to our findings, data from two recent studies conducted in Northern and Southeastern Brazil reported HAdV detection rates of 28.6% and 18.5%, respectively, among children with AGE symptoms 32 , 33 . Another study in Northern Brazil has detected HAdV in 50% of stool samples from hospitalized children with AGE 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Among the non-enteric HAdV, our study found HAdV species C and B with the second and third highest prevalence, respectively. Previous studies performed in Brazil and other developing countries have reported similar results for non-enteric HAdV, with specie C being the most prevalent and specie A, B and D alternating as the second most prevalent 22 , 23 , 29 , 32 , 38 . Moreover, despite an increasing number of studies attributing the detection of non-enteric HAdV types in AGE stool samples as a possible gastroenteritis causative agent 13 , 22 , 23 , 40 , the significance of their detection remains unclear.…”
Section: Discussionsupporting
confidence: 70%
“…Children under 5 years old are the most affected with highest incidence and leading cause of million deaths annually worldwide, occurring mainly in low as well as in middle-income countries [ 2 ]. In Brazil, AGE also presents higher morbidity rates representing a significant cause of death in the first year of life [ 3 5 ]. AGE can be caused by a variety of infectious agents (viral, bacterial, protozoan) as well as non-infectious agents [ 4 ].…”
mentioning
confidence: 99%
“…Previous studies showed other viruses causing gastroenteritis displayed similar viral loads. For instance, a report on children with gastroenteritis found that the adenovirus median viral load was 4.56 × 10 3 genome copies per gram of stools (range 2.14 × 10 2 –1.32 × 10 5 ) [ 22 ]. Another study on patients with gastroenteritis showed that norovirus G1 median viral load was 8.4 × 10 5 genome copies per gram of stools (range: 2.2 × 10 4 –2.9 × 10 10 ) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%